An efficient and concise access to 2-amino-4H-benzothiopyran-4-one derivatives - Li, Peng; Wu, Yongqi; Zhang, Tingting; Ma, Chen; Lin, Ziyun; Li, Gang; Huang, Haihong (Beilstein Journal of Organic Chemistry, 2019)
A highly efficient and convenient protocol was developed to access 2-amino-4H-benzothiopyran-4-ones through a process of conjugated addition–elimination. The sulfinyl group was proved to be the optimum leaving group by thorough investigations on the elimination of sulfide, sulfinyl, and sulfonyl groups at the 2-position of benzothiopyranone. Most 2-aminobenzothiopyranones were obtained in good to excellent yields under refluxing in isopropanol within 36 h. This method is base-free and the substrate scope in terms of electronic properties of the substituents of the benzothiopyranone is broad. The ten grams scale-up synthesis of the representative compounds 4a and 4d was implemented to show the practical application of this reaction, which afforded the corresponding compounds in good yields and excellent chemical purity without requiring column chromatographical purification.
Keywords: 2-amino-4H-benzothiopyran-4-ones; addition–elimination; scale-up synthesis; sulfinyl group